(untitled) (Global Conference on Medical and Health Sciences, 2026)
Background: Iron deficiency anemia (IDA) is the most prevalent nutritional disorder worldwide, affecting approximately 1.2 billion individuals and representing the leading cause of anemia globally. Iron deficiency compromises hemoglobin synthesis, producing characteristic erythrocyte morphological changes and profound impairment of oxygen transport capacity. Objective: This study aimed to systematically evaluate the morphological alterations of erythrocytes and the consequent disruption of oxygen transport function in iron deficiency anemia, elucidating the underlying pathophysiological mechanisms. Methods: A systematic review of 10 peer-reviewed studies published between 2011 and 2024 was conducted, encompassing hematological, biochemical, and electron microscopic investigations in IDA patients and corresponding animal models. Results: IDA was consistently associated with microcytic hypochromic erythrocytes (mean corpuscular volume reduced by 31%; mean corpuscular hemoglobin reduced by 38%), marked poikilocytosis including elliptocytes and target cells, and significantly impaired oxygen transport — evidenced by reduced hemoglobin oxygen saturation (SpO2 −6.4%), decreased oxygen delivery index (DO2I −34%), and rightward shift of the oxyhemoglobin dissociation curve. Erythrocyte deformability was reduced by 27%, impairing microcirculatory